SELECTIVE BIBLIOGRAPHY OF MOMČILO MILANKOV (Heritage, 2025)
The work presents a selective bibliography of Momčilo Milankov, created on the occasion of the 100th anniversary of his birth. In creating the bibliography the mutual catalog COBISS.SR and the mutual catalog COBISS.RS, both monographic and serial publications, were used. The bibliography covers the period from 1956 to 2016 and contains 73 bibliographic units.Bibliographic units are processed according to the International standard for the description of monographic publications ISBD(M) and the International standard for the description of constituent parts of publications ISBD(CR). The units are sorted according to the title in alphabetical order and within that chronologically.
Keywords: bibliography, Momčilo Milankov, COBISS.SR, COBISS.RS.